2019
DOI: 10.1038/s41551-019-0437-9
|View full text |Cite
|
Sign up to set email alerts
|

Computationally guided personalized targeted ablation of persistent atrial fibrillation

Abstract: Atrial fibrillation (AF) -the most common arrhythmia -significantly increases the risk of stroke and heart failure. Although catheter ablation can restore normal heart rhythms, patients with persistent AF who develop atrial fibrosis often undergo multiple failed ablations and thus increased procedural risks. Here, we present personalized computational modelling for the reliable predetermination of ablation targets, which are then used to guide the ablation procedure in patients with persistent AF and atrial fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
220
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(231 citation statements)
references
References 65 publications
9
220
0
2
Order By: Relevance
“…Note that, although we have used a simple and phenomenological aFK model for the LA simulations, our results are consistent with other studies [14,15,53] performed using more detailed atrial myocyte model such as Coutemanche-Ramirez-Nattel (CRN) model [54], which have also reported anchoring of RDs to fibrotic regions. Moreover, we tested our protocol on 3D slab with the CRN atrial cell model and demonstrated similar behaviour of the RDs (further details provided in the S4 Fig).…”
Section: Limitationssupporting
confidence: 90%
“…Note that, although we have used a simple and phenomenological aFK model for the LA simulations, our results are consistent with other studies [14,15,53] performed using more detailed atrial myocyte model such as Coutemanche-Ramirez-Nattel (CRN) model [54], which have also reported anchoring of RDs to fibrotic regions. Moreover, we tested our protocol on 3D slab with the CRN atrial cell model and demonstrated similar behaviour of the RDs (further details provided in the S4 Fig).…”
Section: Limitationssupporting
confidence: 90%
“…Today, radio-frequency catheter ablation is considered to be one of the most effective treatment options, however, the successful outcome is reported to be from 56% to 89% by different clinical trials, moreover, post-operational complications are quite common [2]. On the other hand, several groups reported that personalized mathematical simulation of the action potential (AP) propagation in atria is capable to reproduce clinical measurements and consequently might be used to improve the outcome of the operation by choosing optimal ablation targets [3,4]. One important challenge that remains in the field is inter-subject AP variability present in cardiac electrophysiological recordings [5].…”
Section: Introductionmentioning
confidence: 99%
“…To realize accurate radical treatment, ablation strategies and mapping systems of cardiac excitation are being considered [3][4][5][6][7]. Recently, a patient-tailored computer simulation model was proposed to determine the appropriate ablation site for each patient [8]. However, cardiac ablation is an irreversible procedure, and only non-paroxysmal patients can undergo cardiac ablation and can be treated.…”
Section: Introductionmentioning
confidence: 99%